Antimalarial versus cytotoxic properties of dual drugs derived from 4-aminoquinolines and Mannich bases: Interaction with DNA - Wenzel, Nicole; Chavain, Natascha; Wang, Yulin; Friebolin, Wolfgang; Maes, Louis; Pradines, Bruno; Lanzer, Michael; Yardley, Vanessa; Brun, Reto; Herold-Mende, Christel; Biot, Christophe; Tóth, Katalin; et al. (Journal of medicinal chemistry, 2010)
The synthesis and biological evaluation of new organic and organometallic dual drugs designed as potential antimalarial agents are reported. A series of 4-aminoquinoline-based Mannich bases with variations in the aliphatic amino side chain were prepared via a three-steps synthesis. These compounds were also tested against chloroquine-susceptible and chloroquine-resistant strains of Plasmodium falciparum and assayed for their ability to inhibit the formation of β-hematin in vitro using a colorimetric β-hematin inhibition assay. Several compounds showed a marked antimalarial activity, with IC50 and IC90 values in the low nM range but also a high cytotoxicity against mammalian cells, in particular a highly drug-resistant glioblastoma cell line. The newly designed compounds revealed high DNA binding properties, especially for the GC-rich domains. Altogether, these dual drugs seem to be more appropriate to be developed as antiproliferative agents against mammalian cancer cells than Plasmodium parasites.
Gesehen am 16.11.2023